ФОРМУВАННЯ НАВИЧОК КРИТИЧНОГО МИСЛЕННЯ У ПРОЦЕСІ МЕТОДИЧНОЇ ПІДГОТОВКИ СТУДЕНТІВ-ФІЛОЛОГІВ (Педагогіка вищої та середньої школи, 2022)
The article deals with lingual didactic problems of the development of critical thinking skills of students at lessons on methodic Ukrainian language learning. The author proposes educational methods, which of develop the critical thinking of students-philology.